Perceptions, Challenges and Effectiveness of Modular Distance Learning Approach to The Academic Performance of Humanities and Social Sciences (HUMSS) Students of Botolan National High School - de Ocampo, Norvin D. (Future Science / FSH-PH Publications, 2023)
The COVID-19 pandemic has necessitated a significant shift towards modular distance learning in education systems worldwide. In the Philippines, the Department of Education has developed Self-Learning Modules (SLMs) to ensure quality primary education for all learners during the pandemic. This research study aims to identify the challenges and effectiveness of the modular distance learning approach on the academic performance of Grade 12 Humanities and Social Sciences students at Botolan National High School. Employing a descriptive research design, data were collected through a validated questionnaire and analyzed using weighted arithmetic mean, frequency, percentage distribution, and Pearson-r correlation. The study found that the majority of student-respondents were female, aged 17.31 years old, and achieved very satisfactory academic grades. The students perceived the modular distance learning approach as agreeable, with self-motivation being the most challenging aspect. The ability to express ideas was the most effective aspect, while the ability to answer without pressure was the least effective. The study found no significant relationship between student's perceptions of the modular distance learning approach and their academic performance. Based on the findings, the study recommends using the modular distance learning approach and developing policies to address students' mental health issues. Furthermore, further research is needed to investigate teacher readiness and technology competency, as well as other variables not covered in this study, to improve the effectiveness of the modular distance learning approach. The study demonstrates that despite the limitations caused by the pandemic, modular distance learning can be an efficient alternative to traditional face-to-face education.